ANALISIS KONTRIBUSI ETIKA BISNIS DALAM MENCEGAH PRAKTIK KECURANGAN PADA FUNGSI KEUANGAN - Alfina, Rina Nur; Himmah, Chusnun Niswah Tamamul; Hakim, Adi Lukman (Procuratio : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the contribution of business ethics in preventing fraudulent practices in the financial function through a Systematic Literature Review (SLR) approach. The study reviewed twenty scientific articles published between 2020 and 2025 and searched through Google Scholar as the main database. Selection was carried out using inclusion criteria in the form of scientific articles in Indonesian or English, focusing on business ethics, financial functions, as well as journal articles, while non-article publications, irrelevant articles, or articles published outside the specified time frame were axcluded. Twenty articles passed the PRISMA screening stage and wewe evaluated using methodological quality assessment. The results of the analysis show that business ethics function as a foundation of values and a system of social control. They have the ability to direct organizational policies and individual behavior towards honesty, integrity, and accountability. It has been proven that moral principles such as loyalty, professionalism, transparency, and ethical leadership can help reduce the possibility of errors in financial reporting. However, implementation still faces challenges, particularly poor ethical culture, inconsistent leadership, and lack of protection for whistleblowers. Several studies also emphasize the importance of improving Good Corporate Governance (GCG), ethics training, sustainability, and the use of forensic audit technology as successful methods for improving the application of business ethics. The novelty of this research lies in its comprehensive mapping of the relationship between business ethics, internal control systems, and GCG in the context of financial fraud prevention, as well as the identification of gaps in the implementation of ethics that have rarely been discussed in previous studies. Overall, the study suggests that business ethics can serve as a moral standard and a means of prevention to maintain the credibility and reliability of a company's financial system. Penelitian ini bertujuan untuk menganalisis kontribusi etika bisnis dalam mencegah praktik kecurangan pada fungsi keuangan melalui pendekatan Systematic Literature Review (SLR). Kajian dilakukan terhadap dua puluh artikel ilmiah yang terbit antara tahun 2020 hingga 2025 dan ditelusuri melalui Google Scholar sebagai basis data utama, seleksi dilakukan menggunakan kriteria inklusi berupa artikel ilmiah berbahasa Indonesia atau inggris, fokus pada etika bisnis, kecurangan keuangan, dan fungsi keuangan, serta berbentuk artikel jurnal, sementara publikasi non-artikel, tidak relevan, atau terbit di luar rentang tahun dikeluarkan. Dua puluh artikel memenuhi tahap penyaringan PRISMA dan dievaluasi menggunakan penilaian kualitas metodologi. Hasil analisis menunjukan bahwa etika bisnis bekerja seperti landasan nilai dan sistem pengendalian sosial. Mereka memiliki kemampuan untuk mengarahkan kebijakan organisasi dan perilaku individu ke arah kejujuran, integritas, dan akuntabilitas. Terbukti bahwa prinsip moral seperti loyalitas, profesionalisme, transparansi, dan kepemimpinan etis dapat membantu mengurangi kemungkinan kesalahan dalam laporan keuangan. Namun, implementasi masih menghadapi tantangan, terutama budaya etika yang buruk, inkonsistensi kepemimpinan, dan kurangnya perlindungan bagi pelapor pelanggaran. Beberapa penelitian juga menekankan betapa pentingnya meningkatkan Good Corporate Governance (GCG), pelatihan etika, berkelanjutan, dan penggunaan teknologi audit forensic sebagai metode yang berhasil untuk meningkatkan penerapan etika bisnis. Kebaruan penelitian ini terletak pada pemetaan komperehensif hubungan etika bisnis, sistem pengendalian internal, dan GCG secara terpadu dalam konteks pencegahan fraud keuangan, serta identifikasi kesenjangan implementasi etika yang jarang dibahas pada studi-studi sebelumnya. Secara keseluruhan, penelitian mengatakan etika bisnis dapat berfungsi sebagai standar moral dan cara pencegahan untuk menjaga kredibilitas dan keandalan sistem keuangan perusahaan.